EMPRESA AGRÁRIA: Análise jurídica do principal instituto do Direito Agrário contemporâneo no Brasil - PINHEIRO, Frederico Garcia (2010)
This dissertation aims to present an overview of the legal theory adopted by the enterprise in Brazilian Enterprise Law, and thereafter, further studies specifically the agrarian enterprise, mainly to assess what were the legal innovations that appeared with the validity of the Civil Code of 2002, as well as the corresponding consequences for the Brazilian Agrarian Law that currently has in undertaking its primary agrarian institute.